Attitudes to and use of baby walkers in Dublin. Issue 2 (June 1995) - Laffoy, M.; Fitzpatrick, P.; Jordan, M.; Dowdall, D.
Abstract : OBJECTIVES: To identify the rate of baby walker use, parental attitudes, and associated injuries. DESIGN: Parents of babies attending clinics for developmental assessment were surveyed by self administered questionnaire about their use, attitudes, and history of injuries associated with walkers. SETTING: Dublin, Ireland. SUBJECTS: Parents of 158 babies. RESULTS: Fifty five per cent of the sample used a walker. The main reasons for doing so included babies' enjoyment of them and the fact that the walker was used for an older sibling. Although none of the users listed safety concerns as a reason to stop using the walker, non-users (45%) did so; 12.5% of the users had at least one walker related injury. CONCLUSIONS: Parents of babies who use a walker perceive them as beneficial. However these babies are placed at unnecessary risk. It behoves all health professionals and child carers to alert parents to these dangers and the sale of walkers should be reviewed.